2009
DOI: 10.1159/000277622
|View full text |Cite
|
Sign up to set email alerts
|

Cephalocele: Report of 55 Cases over 8 Years

Abstract: Objective: Cephalocele is a central nervous system (CNS) birth defect. Various CNS and extra-CNS anomalies, as well as prognostic factors have been reported with cephalocele. The aim of this study was to discuss prognostic factors and current possible theories explaining associated anomalies seen in a series of 55 patients with cephalocele. Methods: A retrospective study was performed using the records of 55 children with cephalocele at the Children’s Hospital Medical Center in Tehran, Iran, from October 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 73 publications
3
14
0
Order By: Relevance
“…Our overall 32% incidence of hydrocephalus requiring treatment is very similar to that reported by others, 7,13 as is our 32% incidence among patients with occipital EC. However, whereas others have reported hydrocephalus to be much less common among children with frontal lesions, we found it to be at least as common in this group.…”
Section: Incidence Of Associated Hydrocephalussupporting
confidence: 90%
See 1 more Smart Citation
“…Our overall 32% incidence of hydrocephalus requiring treatment is very similar to that reported by others, 7,13 as is our 32% incidence among patients with occipital EC. However, whereas others have reported hydrocephalus to be much less common among children with frontal lesions, we found it to be at least as common in this group.…”
Section: Incidence Of Associated Hydrocephalussupporting
confidence: 90%
“…23,27 Occipital lesions account for 66%-95% of ECs in North America, Western Europe, and the Middle East. 5,7,11,19,23,25,27 Sincipital lesions predominate in Thailand, Malaysia, Burma, Cambodia, the Philippines, and the Pacific Islands, 3,4,8,16,20,22,27,28 comprising 20 of 21 EC cases in one report. 3 Monteith and coauthors 16 reported ethnic distinctions in New Zealand, with patients of Pacific Island descent having a much higher incidence of sincipital lesions (44%) than those of European origin.…”
Section: Encephalocele Location and Ethnic Predispositionmentioning
confidence: 96%
“…More modern endoscopic endonasal surgical techniques are used in cases were the tumor size and the skull base defects are manageable. These techniques have been very successful in many cases 8,12,13 . In the case presented by us, the tumor was resected en-block using an endoscopic endonasal approach, in a mixed ENT-neurosurgical operating team.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is the only choice for MEC and, depending on the size and location, it can be done through different approaches, such as lateral rhinotomy, bicoronal flap, or intranasal techniques 8,11 . Recent advancement of endoscopic endonasal techniques has made this type of surgery more frequently used, and it has been successful in many cases of nasal MEC 12,13 . ABSTRACT Nasal meningoencephaloceles are rare findings, represented by protrusions of intracranial contents into the nasal cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Neurological deficits are common and depend on the size and types of neural tissues enclosed in the sac. 2 Treatment requires a multidisciplinary approach. …”
mentioning
confidence: 99%